ECONOMIC POLICY IN THE THOUGHT OF ABU ISHAQ AL-SYATIBI: A STUDY ON THE SUSTAINABILITY OF ISLAMIC ECONOMICS - Zein, Ahmad Wahyudi; Bestari, Endar; Siregar, Maya Anggraini; Herlambang, Muhammad Farhan (IJMA (Indonesian Journal of Management and Accounting), 2024)
Talking about Al-Syatibi's thoughts which initiated concepts and thoughts about economics in the fields of production, consumption and distribution. The method used in this research is the library method. This method uses literature such as journals, articles, books, essays and the internet which discuss Al-Syatibi's ideas about Islamic economics. The basis of Al-Syatibi's thinking in the economic field is related to the concept of Maqasid Syariah, and its orientation gave rise to Maslaha Mursalah. Asyatibi's thoughts are considered ideal to be applied in this modern era, because previous thoughts and ideas about economics in those years were considered very irrelevant. Apart from being able to answer the challenges of the times, Maqasid Sharia theory and economic thinking are also believed to be able to bring about positive changes, especially when Muslims themselves are involved in economic activities and are directly involved in economic activities. Al-Syatibi also believes that needs must be based on priorities that are tailored to each level of need.